Revitalisasi Sastra Bonai - Dessy Wahyuni (Kantor Bahasa Provinsi Maluku Utara, 2017)
Globalization myth that emerges nowadays is a globalization process that will create uniform world (homogeneous). The globalization is suspected to be not only to set up point of view of society to the changing world but also to slowly eliminate national identity. Besides, globalization also has brought about a new awareness that pushed aside local values by massive imaging of developed countries. Then, will the local wisdom be able to be a filter of negative impacts of globalization? Bonai ethnic group, one of indigenous people in Riau, is a community that has begun to vanish by the globalization. Even though, the majority of the society still retains their traditional pattern of thinking and lifestyle, the young generation of the ethnic group has begun to leave out their original culture. On the basis of that fact, it is necessary to think about the handling of prevention so that the community will not be disappeared by the ages. an attempt that can be handled is the revitalization of its literature. The main task that is carried out is to inventory Bonai literature. The result shows that Bonai ethnic group has many folklores: oral folklore, half oral folklore, and non- oral folklore. After studied by using analytic descriptive method, the tradition of Bonai ethnic group shows specific cultural enchantment and local identity so that they can be contributed to strengthen learning material as local wisdom (Malay). From cultural perspective, it is known that local wisdom may filter the negative impacts of globalization so that the identity of Bonai ethnic group will be well maintained.